Effect of humic substances, Limosilactobacillus fermentum and their combinations on growth performance, fermentation activity of the microbial population and mucosal immunity in the digestive tract of turkeys - Alena Hreško Šamudovská; Viera Karaffová; Andrej Marcin; Tomáš Mihok; Michaela Harčárová; Jana Koščová; Stanislav Hreško; Lukáš Bujňák (Italian Journal of Animal Science)
In this study, 80 six-week-old turkeys were used to determine the effects of humic substances and the probiotic strain Limosilactobacillus fermentum (L. fermentum) on selected production parameters, and on the concentration of short-chain fatty acids (SCFA) and local mucosal immunity in the caecum. The turkeys were divided into four groups with four replicate pens. The control group received an unsupplemented basal diet and drinking water. The first experimental group (HS) was fed a basal diet supplemented with 5 g of humic substances per kg of diet (0.5%). Probiotic bacteria administered to the second experimental group (LF) were added to the drinking water at a concentration of 1.1 × 108 CFU/bird. The third experimental group (HSxLF) was given a combination of additives. Humic substances and/or probiotics had no significant effect on the production parameters. Administration of L. fermentum led to a significant increase in the concentration of SCFA, mainly acetic acid, with subsequent acidification of the intestinal contents, as well as a significant increase in the gene expression for MUC-2. Similarly, in the combined group, there was significantly higher expression of the MUC-2 gene compared to the control and HS group, but lower than in the LF group. In contrast, significantly lower expression of the IgA gene was found in the HSxLF group compared to the other groups. We concluded that the inclusion of L. fermentum in the drinking water of turkeys may contribute to improving health and maintaining intestinal integrity. The simultaneous addition of humic substances can slightly diminish the effects of probiotics.